ANALISA PENGARUH PRODUCT, PRICE, PLACE, DAN PROMOTION TERHADAP KEPUTUSAN PEMBELIAN DI RUMAH MAKAN AYAM GORENG ECHO: The Effect of Product, Price, Place, and Promotion on Purchas Decision at ‘Ayam Goreng’ Echo Restaurant. - nadia benita putri (Universitas Ciputra Surabaya, 2022)
This research is done to find out the effect of product, price, place, and promotionon purchasing decisions at ‘Ayam Goreng’ Echo restaurant. This research is quantitativeresearch. This research sample is taken by using a non-probability sampling technique. Thetype of non-probability sampling that is selected is purposive sampling. Analysis method thatis used is multiple linear regression analysis. Data source in this research is primary data thatis obtained by distributing 140 questionnaires to customers of ‘Ayam Goreng’ Echorestaurant who have done purchase at least once in the last three months. The results of dataanalysis show that product, price, and promotion partially affect significant on purchasedecision at ‘Ayam Goreng’ Echo restaurant, while place does not affect significant. The resultof determination coefficient shows that product, price, place, and promotion can influence85.7% of purchase decision. The result of this research provides practical implication for themanagement of ‘Ayam Goreng’ Echo restaurant regarding the importance of 4P marketingmix so that marketing strategy that is related to product, price, place, and promotion canimprove customer purchase decision.Key words: Product, Price, Place, Promotion, Purchase Decision